2010
DOI: 10.3390/toxins2071690
|View full text |Cite
|
Sign up to set email alerts
|

Production, Secretion and Biological Activity of Bacillus cereus Enterotoxins

Abstract: Bacillus cereus behaves as an opportunistic pathogen frequently causing gastrointestinal diseases, and it is increasingly recognized to be responsible for severe local or systemic infections. Pathogenicity of B. cereus mainly relies on the secretion of a wide array of toxins and enzymes and also on the ability to undergo swarming differentiation in response to surface-sensing. In this report, the pathogenicity exerted by B. cereus toxins is described with particular attention to the regulatory mechanisms of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
91
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 74 publications
1
91
0
2
Order By: Relevance
“…In this study, we evaluated the possibility of the contamination of several potent food poisoning bacteria and spoilage bacteria in fermented vegetables sold in local markets in Cambodia Fig.1 Schoeni and Wong, 2005;Senesi and Ghelardi, 2010 . Previous study reported that B. cereus was the most prevalent in fermented meat and fish samples in Thailand Ananchaipattana et al, 2012 .…”
mentioning
confidence: 99%
“…In this study, we evaluated the possibility of the contamination of several potent food poisoning bacteria and spoilage bacteria in fermented vegetables sold in local markets in Cambodia Fig.1 Schoeni and Wong, 2005;Senesi and Ghelardi, 2010 . Previous study reported that B. cereus was the most prevalent in fermented meat and fish samples in Thailand Ananchaipattana et al, 2012 .…”
mentioning
confidence: 99%
“…Berbeda dengan hasil pengujian reaksi gram dengan KOH 3% yang menunjukkan bahwa isolat A10 termasuk gram negatif, Bacillus cereus pada umumnya termasuk bakteri gram positif (Senesi & Ghelardi, 2010;Tallent et al, 2012). B. cereus tersebar luas pada berbagai lingkungan, terutama di dalam tanah, dan dapat bertahan lama dalam berbagai kondisi l i n g k u n g a n .…”
Section: Identifikasi Berdasarkan Sekuens Gen 16s Rrna Dan Gyrbunclassified
“…cereus dapat memiliki siklus hidup sebagai saprofit seumur hidupnya, tetapi bakteri ini juga berpotensi sebagai patogen yang menyebabkan sakit pada manusia, terutama sebagai penyebab keracunan makanan yang ditandai dengan diare, gangguan perut, mual atau muntah, yang sebagian besar terjadi pada orang yang kurang sehat, memiliki penyakit kritis atau memiliki kekebalan tubuh yang lemah (McIntyre et al, 2008;Senesi & Ghelardi, 2010;Tallent et al, 2012;). Hasil pengujian Bacillus cereus isolat A10 pada medium skim milk menunjukkan adanya aktivitas enzim protease yang sangat lemah ditandai dengan adanya zona bening yang tipis di sekitar koloni, dibandingkan dengan kontrol positif (Gambar 4).…”
Section: Identifikasi Berdasarkan Sekuens Gen 16s Rrna Dan Gyrbunclassified
“…B. cereus is normally associated with food poisoning that is characterized by either diarrhoea and abdominal distress or nausea and vomiting (Senesi and Ghelardi, 2010). It is also an opportunistic pathogen in immunocompromised patients causing severe endophthalmitis, bacteremia, septicemia, …”
Section: Introductionmentioning
confidence: 99%
“…B. cereus is normally associated with food poisoning that is characterized by either diarrhoea and abdominal distress or nausea and vomiting (Senesi and Ghelardi, 2010). It is also an opportunistic pathogen in immunocompromised patients causing severe endophthalmitis, bacteremia, septicemia, endocarditis, pneumonia, meningitis, gastritis, and cutaneous infections (Senesi and Ghelardi, 2010); Vibrio bacteria is incriminated in mostly gastrointestinal and extra-intestinal diseases in man (Health protection agency, 2007); Enterococcus bacteria are common causes of nosocomial infections (Arias et al, 2010), such as catheter-associated urinary tract infections, endocarditis as well as surgical and burn wound infections (Abranches et al, 2013) ; E. coli bacteria, mostly the shiga toxin producing serotypes cause mild to bloody diarrhoea, haemorrhagic colitis, and hemolytic-uremic syndrome (HUS) (Brooks et al, 2005). Treatment of these various bacterial infections is, however, being hindered by the prevalence of antibiotic resistant strains (Furtula et …”
Section: Introductionmentioning
confidence: 99%